ANALISIS KESELAMATAN DAN EVALUASI RISIKO KECELAKAAN: STUDI KASUS KERUSAKAN DERMAGA AKIBAT KEPUTUSAN OLAH GERAK DI PELABUHAN XYZ - Maulidia, Dian; Ardani, Maskur Faris; Sulistiawati, Sheila; Narantaka, Narantaka; Maruf, Maruf (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
This study aims to analyze the factors that cause damage to the XYZ Port dock on March 10, 2024 due to ship maneuvering decisions in extreme weather. The method used is qualitative with fishbone analysis technique, this analysis leads to an in-depth understanding of the factors that are interrelated and trigger accidents. The results of the analysis showed that the main causal factor was the captain's decision, the limitations of the navigation system and the lack of coordination were the main factors that contributedto this incident. The impact of the quay damage was material loss and disruption of port operations. The XYZ Port dock accident is an important reminder for all relevant parties to increase focus on the safety aspects of shipping. By understanding the causal factors and implementing effective preventive measures, it is hoped that similar accidents can be avoided and the safety of all parties involved in maritime activities can be guaranteed.